Body mass index reference charts for the individuals with Down syndrome aged 2‐18 years - Fabio Bertapelli; Maira R. Machado; Raísa do Val Roso; Gil Guerra‐Júnior (Brazilian Society of Pediatrics, 2017)
Objective: To develop Brazilian growth charts for body mass index (BMI‐for‐age) for individuals with Down syndrome (DS). The secondary objective was to compare the BMI‐for‐age with the Centers for Disease Control and Prevention standards (CDC). Methods: A retrospective and cross‐sectional growth study of 706 youth with DS (56.7% males) was performed in 51 centers in São Paulo state, Brazil. Weight and height were used to calculate the BMI (kg/m2). The LMS method was applied to construct the growth charts. Z‐scores were based on the CDC 2000 growth standards. Results: The BMI‐for‐age reference charts showed excellent goodness of fit statistics for boys and girls with DS aged 2-18 years. At 2 years of age, the mean BMI Z‐scores of boys and girls with DS were lower compared to those of the CDC (Z‐score = −0.2). In contrast, children with DS aged 3‐18 years had higher mean Z‐scores for BMI‐for‐age when compared to those of the CDC (Z‐scores = +0.2 to +1.3). Conclusions: The BMI of Brazilian youth with DS differs from those references established by CDC. These are the first Brazilian BMI‐for‐age charts for individuals with DS and will hopefully guide clinicians and parents in the evaluation and management of the nutritional status in children and adolescents with DS in Brazil.